2014
DOI: 10.1016/j.foodqual.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sugar and fat reduction on perception and liking of biscuits

Abstract: Reducing the fat and/or sugar content in biscuits can be a way to improve their nutritional composition. Seventy-nine consumers of biscuits were recruited to study the impact of these reductions on liking and perception. Four categories of products were selected from a wide range of biscuits available at the French market. Three to six variants of each type of biscuit were produced based on reduced content of sugar, fat or both. Consumers tested the samples under laboratory conditions (6 sessions), recording t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
43
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 20 publications
7
43
0
2
Order By: Relevance
“…252 Moreover, for subjects who ate the set of biscuits with sugar reduction, the intermediate 253 variant and the most sugar-reduced variant were less liked than the standard one, even 254 if significance levels depended on the groups. These results confirm results of 255previous studies which showed that sugar-reduced biscuits are less liked than standard 256 biscuits at low reduction levels, whereas fat-reduced biscuits are less liked than 257 standard biscuits at higher reduction levels(Biguzzi, et al, 2014;Drewnowski, et alin this study, contrary to our expectations, sensory profiles showed 260 that both reduced set of biscuits were not perceived significantly different in terms of fat 261 and sweetness perception. Thus, differences of liking cannot be explained by 262 differences of fat and sweetness perception.…”
supporting
confidence: 87%
“…252 Moreover, for subjects who ate the set of biscuits with sugar reduction, the intermediate 253 variant and the most sugar-reduced variant were less liked than the standard one, even 254 if significance levels depended on the groups. These results confirm results of 255previous studies which showed that sugar-reduced biscuits are less liked than standard 256 biscuits at low reduction levels, whereas fat-reduced biscuits are less liked than 257 standard biscuits at higher reduction levels(Biguzzi, et al, 2014;Drewnowski, et alin this study, contrary to our expectations, sensory profiles showed 260 that both reduced set of biscuits were not perceived significantly different in terms of fat 261 and sweetness perception. Thus, differences of liking cannot be explained by 262 differences of fat and sweetness perception.…”
supporting
confidence: 87%
“…It is also connected with consumers' nutritional awareness (World Health Organization 2003;McVay et al, 2016). Nevertheless, fat and sugar play a crucial role in developing textural and sensory quality of food products especially sweet bakery products (Biguzzi et al, 2014). Sugar gives a sweet taste but also participates in colour and flavour developing as well as cake structure, moisture and air bubble stabilising.…”
Section: Introductionmentioning
confidence: 99%
“…Tarancón et al [12] reported that the information on the labels of the biscuits including olive oil or sunflower oil increased the perception of healthiness and resulted in higher hedonic expectations among the consumers than that on the labels of biscuits including dairy shortening. Biguzzi et al [13] investigated the effect of sugar and fat reduction on perception and liking of biscuits. It was reported that fat reduction was more acceptable than sugar reduction in biscuits.…”
Section: Introductionmentioning
confidence: 99%